Interim public employees and scope of trade union protection - Ávalos, Eduardo (Universidad Nacional del Litoral, 2014)
This work is part of the need to clarify the scope of trade union protection, as a constitutional guarantee in the case of public employees, with special mention of the interim agents whose job status is precarious because its stability is not consolidated . In particular the situation of teachers in public universities is analyzed, and the conflict that occurs when an acting teacher who has trade union immunity, for some reason is unable to continue their internship